Differences in stomatal number per unit area within the same species under different micro-environmental conditions: A working hypothesis - Lleras, Eduardo (Acta Amazonica, 1977)
A of Salisbury's (1927) work on stomata is presented here. He found, basically, that the number of stomata per unit area increased under more xerophytic conditions. This is contrary to prevalent opinion, that postulates that under more humid conditions, the number of stomata can be greater, as there is less danger of dehydration. A hypothesis is presented here that can explain thisThe more xerophytic the conditions, the higher the number of stomata per unit area to permit more efficient gas interchange at those times when relative humidity is high, and danger of excessive dehydration is lowest.